Toroidal variation of the strike point in DIII-D. (January 2019) - Watkins, J.G.; Wang, H.Q.; Barton, J.L.; Wingen, A.; Pace, D.; Moser, A.; Bykov, I.; Masline, R.; Thomas, D.M.; Guo, H.Y.
Highlights: Outer strike point measured by Langmuir probes in DIII-D at 90, 180, 270°. Radial variation of+/−5 mm seen around the torus, peaked at 300°. Strike point variation agrees with previous error field estimates. Abstract: We report measurements of a+/− 5 mm toroidal variation of the outer strike point radial position using an array of three identical Langmuir probes distributed at 90° intervals around the torus (90°, 180°, 270°). The strike point radial location is determined from the profiles of floating potential (Vf ) measured by the three 6 mm diameter domed Langmuir probes as the strike point is swept radially on a horizontal tile surface just outside of the upper small angle slot (SAS1) divertor. Based on the three probe measurements, the strike point variation is consistent with previous error field measurements by Schaffer [1, 2] and estimates by Luxon [3] which indicated the strike point error could appear as an n = 1 radial variation of 4.5 mm at the outer mid plane and thus could be effectively described with a three point measurement. The results are also consistent with field line tracing calculations using the MAFOT code [4] . The small angle slot (SAS1) divertor performance is particularly sensitive to a misalignment with the divertor plasma since enhanced neutral confinement and recycling in the slot and distribution of neutrals along the slot surfaces are important for achieving divertor detachment at the lowest possible core plasma separatrix density. These strike point measurements are discussed with regard to the slot divertor alignment.